Strategi Pembelajaran Akidah Akhlak dalam Membentuk Karakter Siswa di MA Muhammadiyah 1 Jember - Pinandita, Vidi Kresna (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2025)
Learning strategies play a very important role in the implementation of ongoing learning. One of the learning strategies is active learning strategies. Active learning strategies have been applied by aqidah akhlak teachers in shaping students' characters. The formulation of the problem that has been prepared is how the aqidah akhlak learning strategy in shaping students' characters at MA Muhammadiyah 1 Jember. It aims to determine the aqidah akhlak learning strategy in shaping students' characters. A descriptive qualitative approach used in the study, data collection in this study through observation, interviews and documentation. The data analysis technique uses three stages, namely data reduction, data presentation, drawing conclusions. The validity checking technique uses source triangulation techniques. The results of this study are that the learning strategy in shaping students' characters uses active learning strategies. The use of active learning strategies in students is more conducive and effective which is based on more enjoyable PAIKEM learning. Aqidah akhlak teachers at MAM 1 Jember in shaping students' characters apply routine habits, become role models, provide positive encouragement, a supportive environment, so that the implementation of these students becomes more honest, disciplined and trustworthy.